2010
DOI: 10.1007/s11295-010-0322-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage maps of two interspecific grape crosses (Vitis spp.) used to localize quantitative trait loci for downy mildew resistance

Abstract: Two populations (Pop) segregating quantitatively for resistance to downy mildew (DM), caused by Plasmopara viticola, were used to construct genetic maps and to carry out quantitative trait locus (QTL) analysis. Pop1 comprised of 174 F 1 individuals from a cross of 'Moscato Bianco', a susceptible Vitis vinifera cultivar, and a resistant individual of Vitis riparia. Pop2 consisted of 94 progeny from a cross of two interspecific hybrids, 'VRH3082 1-42' and 'SK77 5/3', with resistance traits inherited from Vitis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 50 publications
(56 reference statements)
0
53
2
2
Order By: Relevance
“…While QTL on chromosome 14 have previously been found, the QTL found by Blasi et al (2011) and Venuti et al (2013) do not physically co-locate to the QTL we found on chromosome 14. The QTL on chromosome 7 found using the HC family single phenotype and Bayesian network analyses did not co-locate to one previously found on chromosome 7 by Moreira et al (2011). We have designated the QTL on chromosome 8 from 'Horizon' Rpv17; the QTL on chromosome 11 from 'Horizon' Rpv18; the QTL on chromosome 14 from V. rupestris B38 Rpv19; the QTL on chromosome 6 from 'Horizon' Rpv20; and the QTL on chromosome 7 from 'Horizon' Rpv21.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…While QTL on chromosome 14 have previously been found, the QTL found by Blasi et al (2011) and Venuti et al (2013) do not physically co-locate to the QTL we found on chromosome 14. The QTL on chromosome 7 found using the HC family single phenotype and Bayesian network analyses did not co-locate to one previously found on chromosome 7 by Moreira et al (2011). We have designated the QTL on chromosome 8 from 'Horizon' Rpv17; the QTL on chromosome 11 from 'Horizon' Rpv18; the QTL on chromosome 14 from V. rupestris B38 Rpv19; the QTL on chromosome 6 from 'Horizon' Rpv20; and the QTL on chromosome 7 from 'Horizon' Rpv21.…”
Section: Discussioncontrasting
confidence: 69%
“…(Buonassisi et al 2017). Most loci found have been qualitative (i.e., they explain the majority of the variation in the disease phenotype in a particular experiment), but a few explain only a small portion of the variation (Bellin et al 2009;Blasi et al 2011;Moreira et al 2011;Venuti et al 2013). Resistance dependent on a single dominant locus is not seen as being durable, especially to an air-borne outcrossing pathogen like the one that causes grapevine downy mildew (Buonassisi et al 2017;McDonald and Linde 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of differing phenotypic observation and the lack of contradictory marker information the authors concluded that Rpv12 and Rpv8 are probably not the same locus or allelic variants of the same locus. Moreira et al (2011) reported Rpv13 on chromosome 12, in a V. vinifera 'Moscato Bianco' 9 V. riparia population. Rpv13 mapped close to the reported location for Rpv1.…”
Section: Introductionmentioning
confidence: 99%
“…To date more than thirteen P. viticola major and minor resistance loci have been identified and mapped to chromosomes 4, 5, 7, 8, 9, 12, 14, 17 and 18 (Merdinoglu et al 2003;Fischer et al 2004;Welter et al 2007;Bellin et al 2009;Marguerit et al 2009;Zyprian et al 2009;Moreira et al 2011;Schwander et al 2012). Many of these loci were originally reported without specific gene names some of which were later assigned names in the catalogue of mapped resistance loci (http://www.vivc.de), leaving a few reported loci unnamed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation